John Chilembwe’s Praxis - Jones Hamburu Mawerenga (African Theological Journal for Church and Society)
This study discusses the phenomenon of John Chilembwe’s praxis as a harbinger for the construction of public theology in Malawi. It articulates an apocalyptic, soteriological, ecclesiological, and missional vision in which the church is understood as a socio-political entity in its own right, inaugurated by Christ to publicly exemplify and perform the eschatological new reality of God’s reign here on earth. Qualitative research methods: literature review and historical research were employed. The study established ten findings regarding Chilembwe’s praxis approach: (1) establishing schools, (2) promoting human dignity for all, (3) promoting African land rights, (4) fighting the evils of labour tenancy (thangata system) and taxation, (5) protesting against the involvement of Africans in the First World War, (6) organising the 1915 uprising against the colonial rule which inspired African nationalism that eventually led to the independence of African nations, (7) promoting women’s empowerment, (8) creating an egalitarian society, (9) experimenting with various agricultural initiatives, and (10) using violence to counteract colonialism. In recognition of his visionary, transformational, and servant leadership, the Malawi government declared 15 January as the Chilembwe Day. Also, his portrait was on all Malawi Kwacha notes from 1997 to 2012. Also, the K2000 note has his portrait. Therefore, the study argues that a retrieval of John Chilembwe’s religio-political engagement provides lessons for the task of constructing African public theology. This task entails an articulation of a model of ecclesial political engagement in which the church in Africa demonstrates its own identity and mission as the proclamation and performance of a new order of God’s reign inaugurated in Christ’s death and resurrection. The study has three implications: (1) the explication of the fundamental public contents of the Christian faith drawn from scripture and tradition, (2) the demonstration of Christianity’s public relevance and reasonableness, and (3) an examination and exposition of Christianity’s public meaning, significance, and impact on society.